Types of Attractan Traps for Coffee Berry Borers (Hypothenemus hampei Ferr) in Robusta Coffee Plants (Coffea canephora) - Jimmy Rimbing; Reity Engka; Frangky H. Rorong (AGRIVITA Journal of Agricultural Science, 2024)
The coffee berry borers are the major pest on coffee plants that can reduce the rate of production quality and quantity. An attractant is used to control and suppress the growth of the insects. This research aims to study and identify the combination of methanol and ethanol “cap tikus” as an attractant to protect the plants. This research used a randomized block design using the combinations of methanol-ethanol “cap tikus” with the ratios of 3:1, 2:1, and 1:1. The traps were placed on the coffee trees five times every five days. The combination of methanol-ethanol could be synergistic in attracting female beetles. The highest number of trapped coffee berry borers were on the ratios of 3:1 (28.19%) and 2:1 (27.98%), while the lowest one was found on ethanol “cap tikus” (3.74%). There was an unstable number of trapped borers. The highest trapped insects were on the 15th day, but then it declined on the 20th and 25th days. The trap could also be applied to other types of insects. The combination of methanol-ethanol could be used for monitoring and controlling the beetles, the causal of plant borer.